Potensi Bioetanol dari Alang-alang (Imperata cylindrica) dengan Metode Pembuatan Sederhana - Marco, Martha Aulia (Indonesian Journal of Biomedical Science and Health; Vol 2 No 1 (2022): Juni 2022, 2022)
The availability of energy from fossil fuels is currently running low. The solution to overcome this problem is to develop alternative renewable energy sources such as bioethanol. Bioethanol is alternative energy to replace petroleum. Imperata cylindrica can be used for bioethanol production. The main component of the alang-alang ( Imperata cylindrica ) used for the production of bioethanol is lignocellulose which consists of cellulose, hemicellulose, and lignin. This study aims to study the use of reeds ( Imperata cylindrica ) as bioethanol. This research uses experimental methods through pretreatment, hydrolysis, fermentation, and distillation processes. The results showed that Imperata cylindrica can be used as bioethanol with low alcohol content.